2010
DOI: 10.1007/s13191-011-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment on the Flexural Strength of Denture Base Resin and Tensile Strength of Autopolymerizing Silicone Based Denture Liner Bonded to Denture Base Resin: An In Vitro Study

Abstract: Silicone based denture liners are superior to acrylic based denture liners but it has a problem of failure of adhesion with the denture base. To evaluate the effect on the tensile bond strength of silicone based liner and flexural strength of denture base resin when the latter is treated with different chemical etchants prior to the application of the resilient liner. Rectangular specimens of heat cured PMMA (65 × 10 × 3.3 mm(3)) for flexural strength and (10 × 10 × 40 mm(3)) for tensile strength were fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The resilient denture liners are divided into two groups based on their chemical composition: acrylic polymers and silicone polymers [3][4] . Both have short and longterm use and can be polymerized at room temperature or at high temperatures [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The resilient denture liners are divided into two groups based on their chemical composition: acrylic polymers and silicone polymers [3][4] . Both have short and longterm use and can be polymerized at room temperature or at high temperatures [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with other studies and support the hypothesis that MMA and EA surface treatments could improve the adhesion of silicone-based resilient denture liners. 2,6,11,12 Although the C group achieved an acceptable tensile bond strength, higher than 0.44 MPa, 6,7 according to the literature, these values could rise to 68% after MMA and EA surface treatments, 2,6 Other studies observed an increase in bond strength when these solvents were used as a component of denture liner adhesives, 11,12 which found that the PMMA surface softening by these agents was effective. 11 In contrast with other studies 2,6,20 that found a 45% increase in tensile bond strength, in the present study, the AC protocol did not improve the tensile bond strength between PMMA resin and silicone-based denture liner.…”
Section: Discussionmentioning
confidence: 94%
“…The surface treatment protocols evaluated in this study were previously established in the literature to achieve higher tensile bond strength between PMMA and resilient relining materials. 2,6,11 MMA monomer and AC and EA solutions have been reported as chemical agents used in PMMA surface treatments, 2,6,19,20 as have solvents of primers and adhesives provided by manufacturers. 11,12 However, the effect of these surface treatments on the PMMA surface properties and the relationship with tensile bond strength has not been well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the meta‐analysis indicated that for silicone‐based liners subjected to tensile test, chemical agents are more effective than the other surface treatments. While most of the reviewed literature reported that chemical agents were more effective than the other surface treatments, a few studies reported that it was ineffective or provided similar outcomes to other procedures . Gundogdu et al reported that chemical agents were more effective than sandblasting, laser, and control groups to increase tensile bond strength of silicone‐based resilient lining material to PMMA.…”
Section: Discussionmentioning
confidence: 99%